BINGKAI KEADILAN HUKUM PANCASILA DALAM PERSPEKTIF HUKUM DAN RELEVANSINYA DENGAN KEADILAN DI INDONESIA - Surya Desismansyah Eka Putra (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2014)
Law is a part which always adhere to human being. It is forcing; accepted or not accepted. Take for example, Minah’s case. She stole 3 pieces cacao and she was charged one and a half month of imprisonment, and three month of probationary period. There was also such a stealing case happened in Sidoarjo. The doer was free of any charge. The stealing was considered as a shared responsibility of the society. There are two different dimensions on these two cases. In one hand, lawis obeyed as it is. On the other hand, law is an authentic moral decision. This writing will explain reobservation about the function of law in accordance to moral; the right law enforcement; the relevance of those two cases with law maturity; and the position of Pancasila in seeing those two cases in the context of justice.